Microencapsulação de extrato de beterraba pelo processo de gelificação iônica - Ferreira, Laís Priscila Cavalcante (2018)
In the last decade, beet has attracted much attention as a functional food, with important health promoting effect. It presents in its composition important bioactive compounds, highlighting the betalains, ascorbic acid, carotenoids and phenolic acids. Despite the great nutritional importance, the beet is still not very consumed. The encapsulation by ionic gelation has proven to be an effective technique for obtaining palatable and nutritious products, masking unwanted flavors and preserving nutrients. Considering the above, the objective of the present study was to obtain microcapsules of beet extract by the ionic gelation process and verify the stability during refrigerated storage. From the beet extract the ionic gelation process was performed, obtaining the beet microcapsules and storing them for 28 days in hermetic glass containers at 5 ± 1°C. Analyzes of yield, weight, size, color, soluble solids, moisture, ash, acidity, pH, vitamin C, carotenoids, phenolics, ABTS and betalainas were performed. Regarding the physicochemical characteristics of beet extract with respect to beet microcapsules, there was a significant reduction of soluble solids, betalain, antioxidant capacity, carotenoids and color parameter a*. Vitamin C, phenolics, ash, moisture and pH remained constant. There was an increase in acidity and Hue angle. During refrigerated storage, all parameters except vitamin C were reduced. After 21 days of storage, there was an increase in the permeability of the alginate membrane, resulting in greater migration between the medium and microcapsule compound. It is concluded that the ionic gelation process is a viable technology for the development of products that maintain the nutritional characteristics of the beet and that treatment with ascorbic acid obtained better conservation results of the bioactive compounds.